Development of Leucoma salicis (L.) (Lepidoptera: Lymantriidae) on Populus alba (L.) and Poplar Clone “I-214” - Avtzis, N.D. (ENTOMOLOGIA HELLENICA, 1990)
Tests were made to determine if the phytophagous insect Leucoma salicis (L.) (Lepidoptera: Lymantriidae), preferred Populus alba (L.) or Poplar Clone “I-214” as its host. These tests were based on field observations in experimental plots at the nursery of the Forest Research Institute in Thessaloniki, N. Greece. The observations which continued for a two-year period (1984, 1985) corroborated the high resistance of P. alba to L. salicis. Rearing on this host-plant caused retarded growth, produced lower number of eggs, caused higher larval mortality and generally showed reduced development always, in comparison with the rearing of this insect on leaves of Clone “I-214”.